Food addiction - Akyüz Cim, Emine Füsun; Atlı, Abdullah (Journal of Dependence, 2017)
Although the use of the term “addiction” dates back to 1890, literature studies on the subject are relatively new. In food addiction (FA), the individual develops a behavioral pattern similar to addiction for processed, greasy, sugary, and salty foods. Neurobiological studies on FA show considerable similarities with substance addiction. FA, which has been shown to accompany eating disorders and psychiatric disorders, should be included in treatment guides in order to facilitate diagnosis and treatment. The aim of this article is to raise conceptual awareness regarding diagnosis and treatment strategies for FA..